Multifarious Uses of Vetiver Grass - Ramanjaneyulu, A. V.; Sainath, N.; Ramana, M. Venkata (Chronicle of Bioresource Management, 2023)
Vetiver grass has been recognized for stabilizing the lands susceptible to soil and water erosion thus conserves both the natural resources besides enhancing irrigation water quality. It is one of the best agrostological measures for protecting the contours. It has an exceptional ability to withstand extreme climatic conditions, sodicity and alkalinity. It is a good candidate for phytoremediation of polluted and contaminated soils. The oil extracted from its roots is widely used in industrial and medical fields. Overall, it is regarded as a dynamic tool for mitigating numerous environment and agriculture related challenges. Though a manual entitled “Vetiver Grass - A Hedge against Erosion (or known as ‘little green book’) by John Greenfield deals with technical aspects of it’s cultovation in detail, we made an effort to synthesize the available information on numerous applications of this soil binding grass and benefits in achieving sustainable agricultural development.